Nilai gizi dan profil asam amino ikan etong (Abalistes stellaris) dan ikan tongkol (Euthynnus affinis) - Jatfitri Veda Januarita; Dwi Ishartani; Woro Setiaboma; Dita Kristanti (AGROINTEK, 2022)
Fish is one of the animal foods rich in protein, minerals, fatty acids, and essential amino acids. Differenced color muscles (white and red) affect the protein, amino acid profile, and minerals content of fish. The research on etong fish (Abalistes stellaris) and tuna (Euthynnus affinis) in Indonesia is limited in their nutritional value. This study aims to determine the nutritional value, minerals, and amino acid profiles in A. stellaris and E. affinis from Subang, West Java. Samples were obtained from Blanakan, Subang, West Java, which were caught from October to December 2020. The analysis carried out in this study included proximate pH, minerals, and amino acids of fish. The protein, fat, iron, calcium, and zinc contents in E. affinis were higher than A. stellaris. A. stellaris contained  79,64% moisture, 0,95% ash, 18,89% protein, 0,43% fat, 0,25% carbohydrate, 0,72 mg/100 g iron, 1,42 mg/100 g calcium, dan 0,95 mg/100 g zinc. E. affinis contained  77,50% moisture, 0,87% ash, 20,27% protein, 0,96% fat, 0,66% carbohydrate, 1,98 mg/100 g iron, 14,83 mg/100 g calcium, dan 1,11 mg/100 g zinc. The amino acid profile of E. affinis is more complete than A. stellaris, where the methionine, phenylalanine, arginine, histidine, and tyrosine were not detected in A. stellaris. The amino acid content of E. affinis was significantly higher than A. stellaris, except for the amino acids leucine and arginine. This research showed that E. affinis had higher nutritional potential than A. stellaris. So E. affinis has the potential as a good source of protein and minerals.